FREQUENCY OF HEPATITIS B, HEPATITIS C AND HIV INFECTIONS AMONGST EMPLOYEES OF A UNITED NATIONS PEACE KEEPING MISSION: Employees of United Nations - Arshad, Abdul Rehman; Khan, Imran; Ibrahim, Aqeel (Pakistan Armed Forces Medical Journal, 2014)
Objective: To determine the frequency of HBsAg, anti HCV antibodies and anti HIV antibodies amongst UNAMID employees attending our dental clinics.Study Design: Observational study.Place and duration of study: This study was carried out at Pakistan Field Hospital Level III, Nyala, Sudan from 1 Oct 2011 to 31 Dec 2011.Patients and Methods: All patients who were to undergo some dental surgical procedure had their HBsAg, anti HCV antibodies and anti HIV antibodies status checked by immunochromatographic technique prior to the procedure.Results: Out of the 156 patients studied, HBsAg was detectable in 7.7% and anti HCV antibodies in 1.3% of the patients. None tested positive for anti HIV antibodies.Conclusion: Hepatitis B and C infections do occur in our patient population. However, HIV infections are not seen.